Isobutane/Butene Alkylation:regeneration of solid acid catalysts - Querini, Carlos Alberto (2000)
The regeneration of Y-zeolite catalysts used during the isobutane alkylation reaction is studied. Coke is characterized by temperature-programmed techniques and measuring the H/C ratio. The coke deposited under supercritical conditions is very similar (TPO profile and amount) to the coke deposited in liquid phase. The regeneration was carried out in many ways. Air was used for heating with at a low rate, and holding the temperature at low values for long times. Platinum was incorporated in the zeolite to catalyze the coke combustion or to provide an additional route for coke gasification, such as hydrogenation. Ozone was used to remove most of the coke, followed by a second step with H2 or He. Hydrogen peroxide was studied as an alternative low-temperature oxidation compound. It was found that the ozone treatment, followed by a hydrogen treatment, is an effective way to regenerate this microporous catalyst. The ozone not only eliminates a large fraction of the coke but also changes the characteristics of the small amount of coke left on the catalyst, making it easier to be burnt. The treatment with hydrogen peroxide at 90°C also removes a large fraction of coke, but without changing significantly the characteristics of the coke left after the treatment.